A Comparative Study of the Antihypertensive Agents on Serum Liver Enzymes ALT, AST and ALP of Hypertensive and cardiac Patients - Aisha Javaid; Ruqaiya Hasan; Aisha Zohra; Zahir Hussain (Journal of Basic & Applied Sciences, 2021)
Present study is done to compare serum Liver enzymes including Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST) and Alkaline Phosphatase (ALP) in hypertensive and cardiac patients. 24 patients were divided into 4 groups according to their treatment with 4 different types of antihypertensive drugs. Group I treated with Beta-blockers (1+1). Group II treated with ACE-Inhibitor once a day. Group III treated with Nitrates once a day. Group IV is taking Diuretics once a day. Data showed non-significant difference in serum ALT concentration in all groups. A significant rise (p< 0.05) in serum AST and ALP levels among hypertensive and cardiac patients is observed, ranging from 24.63-47.33U/L and 110-2484 U/L respectively when compared with normal controls. Thus, not only the risk of cardiac diseases in future might be predicted by altered levels of enzymes ALT, AST and ALP in serum but their concentrations should be monitored during the treatment of cardiac diseases to minimize the risk of cardiac arrest.